Association between teenage pregnancy rates and the age and sex of general practitioners: cross sectional survey in Trent 1994-7. Issue 7238 (25th March 2000) - Hippisley-Cox, Julia; Allen, Jane; Pringle, Mike; Ebdon, Dave; McPhearson, Marion; Churchill, Dick; Bradley, Sue
Abstract: Objective: To examine variations in teenage pregnancy rates in Trent region and to determine possible associations with local general practice characteristics such as the age and sex of the doctors. Design: Cross sectional survey. Setting: All 826 general practices in Trent region in existence between 1994 and 1997. Subjects: All pregnancies of teenagers aged 13 to 19 between 1994 and 1997 that resulted in an admission to an NHS hospital. Main outcome measures: Pregnancy rates for teenagers aged 13 to 19 and general practice characteristics: presence of a female or young doctor (under 36 years old), number of whole time equivalent practice nurses, Townsend score, vocational training status, list size per whole time equivalent doctor, fundholding status, and partnership size. Results: On multivariate analysis, lower teenage pregnancy rates were associated with the presence of a female or young doctor and more nurse time. Practices in deprived areas had higher teenage pregnancy rates. Conclusion: General practices with female doctors, young doctors, or more nurse time had lower teenage pregnancy rates. The findings may have implications for the mix of health professionals within primary care.